2018
DOI: 10.1136/bjophthalmol-2018-312453
|View full text |Cite
|
Sign up to set email alerts
|

Safety of 5914 intravitreal ziv-aflibercept injections

Abstract: This constitutes the largest pooled safety report on IVZ use and includes patients from 14 centres distributed across the globe. It shows that IVZ has an acceptable ocular and systemic safety profile with incidences of adverse events similar to those of other vascular endothelial growth factor inhibitory drugs. The analysis supports the continued use of IVZ in various retinal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Additionally, the improvement in BCVA and the reduction in CMT after injection were achieved in both groups, with statistical significance that reflects the efficacy of the new drug in myopic CNV patients with a high safety profile and low cost. This finding was quite similar to those from recent studies performed on ziv-aflibercept on a larger number of patients [ 32 , 33 ] that discussed the application of ziv-aflibercept in different retinal diseases and detected a reasonable safety profile for the drug comparable with those of other anti-VEGF agents. Moreover, Braimah et al [ 11 ] studied the efficacy of ziv-aflibercept on retinal diseases other than AMD, such as high myopia, macular telangiectasia, central serous chorioretinopathy, choroidal osteoma, choroiditis, Best’s disease and idiopathic macular degeneration, and reported a marked reduction in CMT and a moderate improvement in BCVA.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the improvement in BCVA and the reduction in CMT after injection were achieved in both groups, with statistical significance that reflects the efficacy of the new drug in myopic CNV patients with a high safety profile and low cost. This finding was quite similar to those from recent studies performed on ziv-aflibercept on a larger number of patients [ 32 , 33 ] that discussed the application of ziv-aflibercept in different retinal diseases and detected a reasonable safety profile for the drug comparable with those of other anti-VEGF agents. Moreover, Braimah et al [ 11 ] studied the efficacy of ziv-aflibercept on retinal diseases other than AMD, such as high myopia, macular telangiectasia, central serous chorioretinopathy, choroidal osteoma, choroiditis, Best’s disease and idiopathic macular degeneration, and reported a marked reduction in CMT and a moderate improvement in BCVA.…”
Section: Discussionsupporting
confidence: 91%
“…Serious systemic adverse events included 2 cases of CVAs, 2 deaths and 1 myocardial infarct were also noted, but could not be definitively linked to the use of ziv-aflibercept. It was concluded that the safety profile of ziv-aflibercept was similar to that of commercially available anti-VEGF IVT agents [44].…”
Section: Ziv-afliberceptmentioning
confidence: 92%
“…Any ocular or systemic side effects were noted and were considered injection or procedure related if occurred within 1 month of intravitreal injections. [20]…”
Section: Methodsmentioning
confidence: 99%